S-Wave Velocity Structure beneath Southwest North America from Seismogram Comparisons of the Mexico Earthquake on 22 June 1997 - Bagus Jaya Sentosa (Institute for Research and Community Services (LPPM) ITB, 2008)
This research investigates earth structure beneath the Southwest North America landmass, especially between Mexico and California. Models based on S wave velocities for this area were obtained by carrying out seismogram fitting in time domain and three Cartesian components simultaneously. The data used is from an event, coded as C052297B that occurred in the state of Guerrero, Mexico and it was fitted to synthetic data computed with the GEMINI program at TS network stations. Earth model IASPEI91 and SPREM were used as input to create the synthetic data. Real and synthetic seismograms were subjected to a low-pass filter with a frequency corner of 20 mHz. Waveform analysis results show very unsystematic and strong deviations in the waveform, arrival times, amount of oscillation and the height of the wave amplitude. Discrepancies are met on S, Love, Rayleigh and ScS waves, where the stations epicentral distances are below 300. Deviation in analysis waveform because of the usage of model 1-D of SPREM and IASPEI91, because the 1-D was a kind of average value an elastic property at one particular depth of global earth. With the method of waveform analysis we can see how sensitive waveform is to structures within the layers of the Earth. To explain the discrepancies, a correction to the earth structure is essential. The corrections account for the thickness of the crust, speed gradient of h, the coefficient for the h and v in the upper mantle for surface wave fitting, a small variation of the S speed structure at a layer under the upper mantle above 771 km for S wave fitting, and a small variation at the base the mantle layers for ScS wave fitting. At some stations, a correction for S speed structure have yielded P wave fitting. Results of this research indicate that the 1-D earth model obtained through seismogram fitting at every hypocenter-observation station pair is unique. The Swave velocity on the upper mantle has strong negative anomalies. This paper criticized the previous earth models in the same area, which have been published by other seismologists, by analyzing the seismogram of C052297B earthquake in the TS seismological network station.